Economic value of ecosystem services of Gosaba estuarine ecosystem of Sundarbans - Ekka, Anjana; Pandit, Arun; Katiha, P. K.; Biswas, D K (Journal of the Inland Fisheries Society of India, 2021)
Inland open waters like any other natural resources are complex, multi-functional, and provide a number of ecosystem services contributing to humanwelfare. However, we often underestimate their values since we get most of the services for free. Therefore, economic valuation could be a powerful tool for realizing the actual values of these precious natural resources and thereby contributing to shaping the policies governing their conservation and sustainable utilization. The present study attempted to value some of the ecosystem services of Gosaba Island which is an estuarine ecosystem situated in Indian Sundarbans. For the study, primary and secondary data were collectedfrom the different stakeholders. Out of the several ecosystem services in the selected ecosystem, seven services viz, fisheries, eco-tourism, agriculture, nontimber forest produce (NTFP), dike protection function of mangroves, carbon stored and option use value (through WTP) were considered for the valuationexercises. Different valuation techniques like market price, revenue generation, Travel Cost Method, Contingent Valuation were applied. It was estimated thatthe minimum value of the six goods and services were Rs.69,527 lakh per annum, among them carbon store value, eco-tourism, dike protection function ofmangroves. In addition, the option use value was estimated to be Rs. 5.82 lakh. Fisheries, agriculture were the major components. The study is important inunderstanding the value of the ecosystem services which may help in their conservation.Key words Valuation; Estuary; Sundarbans